Analysis of the Water Quality of the River in West Java as the Raw Water for Drinking Water - Djembarmanah, Rachmawati Sugihhartati; Salsabila, Gina (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
The quantity of raw water from springs, groundwaters, and rainwaters has been decreasing nowadays. This has mostly made river water to be used as the raw water to be treated for drinking water by PDAMs. However, in 2020, 52 rivers in Indonesia were polluted. Therefore, it is necessary to analyze the quality of the river water to ensure that the water conforms with the standards of the Indonesian Government Regulation Number 22 of 2021 (class 1). This study was done to study the water quality i.e. DO, TSS, and total coliform in 9 sampling points in Citarum, Cimanggu, Cibogo, Citonjong, Ciwayang, and Cigugur Rivers in West Java. Grab samples were collected and were analyzed in the laboratory. The results were then compared with the standards. DO in the Citarum River (= 3.66 mg/L) and Cimanggu River (= 3.64 mg/L) samples were below the standard which might result from the domestic waste generated by the housing settlements, schools, and hospital existed around the sampling points. Total coliform in the upstream of the Cibogo River sample was above the standard; which could be caused by the domestic waste produced by the housing settlements and the fishing area located around the sampling point.